LITERASI DIGITAL DALAM PEMBELAJARAN: PELATIHAN BAGI SISWA DAN GURU SMK NGURAH RAI DAN PKBM WIDYA CHANDRA - I Gde Putu Agus Pramerta; I Ketut Wardana; Ida Ayu Candrawati (Jurnal Bakti Saraswati (JBS), 2025)
Digital literacy training in learning for students and teachers at Ngurah Rai Vocational School and the Widya Chandra Community Learning Activity Center (PKBM) was carried out as an effort to increase the digital competence of students and educators in facing the demands of the digital era. This activity aims to provide understanding and skills in the use of information and communication technology (ICT) to support a more interactive, creative and independent learning process. Training methods include lectures, discussions, direct practice, and mentoring, with materials including introduction digital tools And plarform which can be used to support the learning process, management of learning content, ethics and security in the use of technology. Participants consisted of 19 students and 5 teachers from Ngurah Rai Vocational School and PKBM Widya Chandra. Evaluation results show an increase in participants' understanding and digital literacy skills, as well as enthusiasm in integrating technology into learning. It is hoped that this activity can be the first step in building a digital culture and producing a positive literate generation and supporting the learning process at both institutions.